Magnesium Sulphate for Fetal Neuroprotection at Imminent Risk for Preterm Delivery: A Systematic Review With Meta-analysis and Trial Sequential Analysis. Issue 2 (June 2021) - Wolf, H.T.; Huusom, L.D.; Henriksen, T.B.; Hegaard, H.K.; Brok, J.; Pinborg, A.
Abstract : ( BJOG . 2020;127:1180–1188) Preterm birth is associated with higher risk of cerebral palsy (CP) and other complications. Magnesium sulfate (MgSO4) may decrease risk of CP when taken immediately before preterm birth. A recent trial investigated the neuroprotective functions of MgSO4 . This updated systematic review, meta-analysis and trial sequential analysis (TSA) assessed the effects of MgSO4 administered before preterm birth to prevent CP in neonates.